Design of IoT Based Electrical Parameter Monitoring System using NodemCu V3 and PZEM-004T V3 Sensor - Rangkuti, Tegar Hilmansyah; Martiano, Martiano (Tsabit Journal of Computer Science, 2025)
This research aims to design an electrical parameter monitoring system based on the Internet of Things (IoT) using NodeMCU V3 and the PZEM-004T V3 sensor. The system is designed to monitor various electrical parameters in real-time, including voltage, current, power, power factor, frequency, and energy consumption with high accuracy. Data collected by the PZEM-004T sensor is transmitted to Blynk via a Wi-Fi connection facilitated by NodeMCU V3. Users can access this information through Blynk, enabling efficient energy consumption management. By integrating IoT technology, this system provides a practical solution for monitoring and controlling electricity usage in household environments. The implementation of this system is expected to help users optimize energy consumption and effectively reduce electricity costs.